2020
DOI: 10.1002/app.50084
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulation of Rhodopseudomonas palustrisKTSSR54 using beads from alginate/starch blends

Abstract: Alginate beads are a promising carrier for biofertilizer delivery, but still possess drawbacks of low mechanical strength and bead shrinkage that result in poor appearance and inadequate cell protection. Blending alginate with starch was proposed as a solution to these problems, and here alginate hydrogels were prepared using a 2% (w/v) alginate dispersion blended with varying contents of gelatinized starch (0–5% w/v). The interaction produced a viscosity synergism that increased the complexity of the matrix n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 44 publications
1
7
1
Order By: Relevance
“…Thus, our results are visually consistent, since, as observed in Figure 4, all the samples with alginate at 2% (w/w) and cornstarch at 2% (w/w) presented a spherical shape. A similar behavior was reported by Rohman et al [49], who encapsulated Rhodopseudomonas palustris KTSSR54 using alginate/cornstarch beads through the ionic gelation technique, since the authors indicated that a cornstarch concentration between 3% (w/v) to 4% (w/v), with alginate at 2% (w/v), allows for good sphericity (SF < 0.05) in the alginate beads. For aw and moisture content, there are significant differences between the samples, with a continuous decrease from the initial solution until cycle 3, with values from 0.98 to 0.92, and from 86.1% to 73.6%, respectively.…”
Section: Characterization Of Calcium Alginate Hydrogel Beadssupporting
confidence: 80%
“…Thus, our results are visually consistent, since, as observed in Figure 4, all the samples with alginate at 2% (w/w) and cornstarch at 2% (w/w) presented a spherical shape. A similar behavior was reported by Rohman et al [49], who encapsulated Rhodopseudomonas palustris KTSSR54 using alginate/cornstarch beads through the ionic gelation technique, since the authors indicated that a cornstarch concentration between 3% (w/v) to 4% (w/v), with alginate at 2% (w/v), allows for good sphericity (SF < 0.05) in the alginate beads. For aw and moisture content, there are significant differences between the samples, with a continuous decrease from the initial solution until cycle 3, with values from 0.98 to 0.92, and from 86.1% to 73.6%, respectively.…”
Section: Characterization Of Calcium Alginate Hydrogel Beadssupporting
confidence: 80%
“…Khlibsuwan et al found that gelatinized starch yielded higher encapsulation efficiency than ungelatinized native starch [ 112 ]. To address the disadvantages of alginate microbeads, such as low mechanical strength, microbead shrinkage, poor appearance, and insufficient cell protection, the alginate hydrogels were prepared by mixing alginate with cassava starch [ 99 ]. The result showed that the encapsulation efficiency increased linearly with the increasing cassava starch content, which is similar to previous reports crediting starch addition with increasing encapsulation efficiency [ 100 , 112 ].…”
Section: Alginate-based Probiotics Deliverymentioning
confidence: 99%
“…This is the result of the hydroxyl interaction of the starch molecule with the carboxyl group of the alginate through intermolecular hydrogen bonding. Such interaction produces a viscosity synergistic effect in the alginate/starch mixture, thereby increasing the complexity of the matrix network [ 99 , 112 ].…”
Section: Alginate-based Probiotics Deliverymentioning
confidence: 99%
“…Many biopolymers, such as carbohydrates (e.g., sodium alginate, gellan gum, xanthan gum, chitosan, starch), proteins (e.g., gelatin, whey protein), and lipids (e.g., types of butter) [ 1 ], are useful in encapsulation technology, and carbohydrate polymers now play a key role [ 2 , 3 ]. The encapsulation of microorganisms is attracting attention as a method to improve the efficiency of beneficial microorganisms [ 4 , 5 , 6 , 7 ]. This encapsulation involves coating particles containing active microorganisms with layers of other materials that protect the viability and activity of the microbes.…”
Section: Introductionmentioning
confidence: 99%